2000
DOI: 10.1097/00003246-200007000-00032
|View full text |Cite
|
Sign up to set email alerts
|

Protein C substitution in sepsis-associated purpura fulminans

Abstract: This article provides encouraging results on the use of PC substitution in meningococcal purpura and presents new data on the administration of this drug to patients with septic purpura caused by other bacterial species. By clinical judgment, PC limited the extent of tissue necrosis. The small number of patients does not allow for any conclusions on the potential effect of PC on mortality. A controlled and randomized study with a larger number of patients is needed before any recommendations can be given on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(51 citation statements)
references
References 24 publications
1
46
0
2
Order By: Relevance
“…PC administration to 12 patients (17 to 68 years old) with purport fulminates in an uncontrolled fashion resulted in an improvement in clinical status. 45 A large randomized trial of activated PC administration to adult patients with severe sepsis demonstrated a significant (19.4%) reduction in relative risk of mortality in the PC-treated group, compared to control, although a trend for increased risk of bleeding occurred in those receiving activated PC. 46 Infants have been included in reported studies of antithrombotic agents.…”
Section: Treatment Of Coagulation Disturbancesmentioning
confidence: 99%
“…PC administration to 12 patients (17 to 68 years old) with purport fulminates in an uncontrolled fashion resulted in an improvement in clinical status. 45 A large randomized trial of activated PC administration to adult patients with severe sepsis demonstrated a significant (19.4%) reduction in relative risk of mortality in the PC-treated group, compared to control, although a trend for increased risk of bleeding occurred in those receiving activated PC. 46 Infants have been included in reported studies of antithrombotic agents.…”
Section: Treatment Of Coagulation Disturbancesmentioning
confidence: 99%
“…(5) Few authors have tested the utility of PCc in young patients with purpura fulminans and/or meningitis and few reports exist on the use of PCc as an alternative treatment to rhAPC in adult patients affected by sepsis or septic shock, in which rhAPC was contraindicated by a high risk of bleeding. We previously reviewed (6-8) the published experience with PCc in 66 adults (6)(7)(8)(9)(10)(11)(12)(13)(14) and 118 children (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) without congenital defects. Considering the market withdrawal of rhAPC, the recent publication of further case series (26)(27)(28)(29) and the presence of reports (30)(31)(32)(33) that were not identified in the previous reviews, we decided to update the systematic review and concisely summarize the overall results.…”
mentioning
confidence: 99%
“…It has been associated with improvement in coagulation screening and limb necrosis in case-series of meningococcal purpura, 32 however, the RESOLVE (randomized controlled trial of activated protein C in children with severe sepsis) trial has recently been stopped because of failure to meet the primary endpoint. 33…”
Section: Glycemic Controlmentioning
confidence: 99%